Risk of Stillbirth after Infertility Treatment in the United States: 2014-2017 - Deepa Dongarwar, MS (International Journal of Maternal and Child Health and AIDS, 2020)
To estimate the risk of stillbirth following infertility treatment in the United States (US), we analyzed data from the US Natality and Fetal Death files from 2014 to 2017. We built Cox proportional regression models to generate adjusted hazard ratios (HR) for the risk of stillbirth among women who utilized various modalities of infertility treatment within the study period. Women who used any infertility treatment and, specifically, assisted reproductive technology (ART), had an elevated risk of stillbirth (HR: 1.21, 95% CI:1.09 -1.33) compared to women who did not use ART. We concluded that in this population, the risk of stillbirth was elevated among women using infertility treatment.